The "nocturnal side of science" in David Friedrich Strauss's Life of Jesus critically examined - Fabisiak, Thomas (Emory studies in early Christianity, 2015)
A close look at how Strauss's engagement with popular and scholarly controversies influenced his study of the Gospels. David Friedrich Strauss's Life of Jesus Critically Examined is known as a monumental contribution to the critical, scientific study of religion and Christian origins. It was widely read and influenced literary and historical research on the Bible as well as critical philosophy between Hegel and Nietzsche. Less well-known are Strauss's writings from the same period on "the nocturnal side of nature," paranormal phenomena such as demon possession, animal magnetism, and the ghost-seeing of Frederike Hauffe, the famous "Seeress of Prevorst."--Publisher